PENYUSUNAN LAPORAN KEUANGAN PADA PD XXX SESUAI SAK EMKM - Henny Wirianata (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Community service activities carried out to PD XXX is the first carried out by the Untar Team. Based on the results of initial observations and discussions, PD XXX sees a need to get a correct understanding of the accounting cycle and the preparation of financial statements. Since it began operating, PD XXX has not been able to present complete information about the financial condition of the company. The Untar team provides training about how to prepare the correct financial statements in accordance to MSME Accounting Standards. With the training, PD XXX is expected to get more adequate knowledge about financial statements and can apply that knowledge in the process of preparing financial statements. The training was given 3 times, in October and November 2021. In training 1 and 2, PD XXX are given exposure about accounting cycles and financial statements for MSME. In training 3, the Untar Team explained the format of financial statements that are in accordance with the operational activities of PD XXX and the needs of PD XXX in the future.